1998
DOI: 10.1073/pnas.95.21.12580
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline control of prion protein transgene expression modulates prion disease in mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 33 publications
(30 reference statements)
1
94
2
Order By: Relevance
“…inoculation with 2 mg brain tissues from BSE-C-infected cattle (2). It is noteworthy that the Tg650 mice express human PrP-129M at five to eight times the normal level, and high PrP levels are known to increase prion transmissibility (9,17,22). Inefficient BSE-C transmissions (0 to 30%) in Tg mouse lines of other genetic backgrounds expressing human PrP-129M at one or two times the normal level have also been reported by different groups (1,4).…”
Section: Discussionmentioning
confidence: 79%
“…inoculation with 2 mg brain tissues from BSE-C-infected cattle (2). It is noteworthy that the Tg650 mice express human PrP-129M at five to eight times the normal level, and high PrP levels are known to increase prion transmissibility (9,17,22). Inefficient BSE-C transmissions (0 to 30%) in Tg mouse lines of other genetic backgrounds expressing human PrP-129M at one or two times the normal level have also been reported by different groups (1,4).…”
Section: Discussionmentioning
confidence: 79%
“…A few transgenic strains were then transferred to a FVB/N inbred genetic background. To induce expression of human ATAXIN1 in the brains of transgenic mice, the PrP-tTA (F959 line) (Tremblay et al, 1998) transgenic line was used, which expresses tTA at high levels in all brain regions (Boy et al, 2006).…”
Section: Production and Maintenance Of Tet Transgenic Micementioning
confidence: 99%
“…Interestingly, the development of spongiform pathologies requires the presence of both isoforms PrP-res and PrP-sen (9), the level of PrP-sen expression being an essential factor in the pathology (10). In experimental transmissions with transgenic mice, it was found that increasing the number of PrP gene copies led to a decreased incubation time of the disease (11,12).…”
Section: Transmissible Spongiform Encephalopathies (Tse)mentioning
confidence: 99%